Synthesis and Characterization of Carboxymethyl Derivatives of Sago (Metroxylon sagu) Starch. Issue 1 (July 2015) - Othman, Zainon; Hashim, K.; Sabariah, K.; Nasir, M. H. Abd; Hassan, A.; Haryono, Agus; Azuma, Jun‐ichi
Summary Synthesis of carboxymethyl starch (CMSS) from sago (Metroxylon sagu), an important agricultural commodity of Malaysia, was conducted in 30 L reactor vessel using isopropanol as the non‐aqueous medium. CMSS of degree of substitution (DS) 0.24, 0.40, 0.54 and 0.80 was prepared by varying the molar ratio of sodium hydroxide and sodium monochloroacetate to anhydroglucose units including reaction time. Substitution of the hydroxyl groups on the native starch with carboxymethyl group was confirmed using Fourier transform infrared. All prepared samples were water‐soluble at room temperature, producing high paste clarity. Carboxymethylation markedly reduced viscosity of CMSS compared to native sago. The particle size distribution also displayed increase in the granule size range compared to native sago. However X‐ray diffractometry of CMSS revealed loss of crystallinity. Scanning electron microscopy showed that the granular smooth appearance of native starch was mostly distorted after carboxymethylation process at higher DS values. The synthesis of carboxymethyl sago starch with different degrees of substitution will add value to the sago industry as new functional biomaterial with potential application in the food and non‐food industry.<inline-graphic xlink:href="ark:/27927/pgj25z0m0j9" content-type="masy201550319-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />